Gender and Environmental Justice : An Ecofeminism review - Taouti, Meriem Amira; Aribi ,Brahim (Faculty of Letters and Foreign Languages Department of English, 2024)
Ecofeminism is a philosophical and social movement that seeks to bridging the gap between gender and environmental justice for a more sustainable future that has always been a philosophical a societal concern. Therefore, this ecofeminist study focuses on the relationship between women and nature as reflected in the work of Susan Griffin “ Woman and Nature : the roaring inside her.” highlighting the ways in which patriarchal systems have contributed to the degradation of both. It is possible that ecofeminism involves the oppression of both women and nature the same time and attempts to overcome it through questioning male dominance and ensuring environmental preservation.A literature review of ecofeminist theories and previous studies done about the subject will form the basis of this research’s qualitative nature. Susan Griffin’s and other author’ works provide striking illustrations of how literature can inspire social change and build a more sustainable future. This study contributes to the current body of knowledge on ecofeminism by emphasizing the significance of connecting gender and environmental justice. It highlights the importance of recognizing and challenging patriarchal structure t It underscores the need for both recognizing and challenging a patriarchal structure that perpetuates the subjugation of women and nature with a view to achieving gender equity and sustainability for the future of society as a whole, based on the understanding and encouragement of gender equality and environmental sustainability